Analisis Kebutuhan Sistem Pendingin pada Ruang Kerja di PT. Fesco Offshore Kalimantan Timur - Saneta, Chelsea Orisa; Panjaitan, Jonery Hardianto; Matondang, Ridho Wiranata (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Cooling machines are quite well known to everyone, especially those in tropical areas. As is known, tropical areas have quite hot temperatures so that cooling devices are needed to cool the room. The importance of the cooling system in everyday life, both at home, in the office and in other places that require air conditioning. Therefore, the author is interested in conducting research entitled "Analysis of Cooling System Needs in the Workspace at PT. Fesco Offshore East Kalimantan". The research was conducted from June to July 2024 at PT. Fesco Offshore East Kalimantan. The company is located at Ruko Mall Fantasi Block AA-2A No. 6 South Balikpapan, East Kalimantan, a company engaged in the field of HVAC unit installation services. The object of research in writing this journal is focused on the 1st floor workspace. The research methods used are literature methods, observation methods and documentation. The variables used are independent variables, dependent variables and control variables. The 1st floor workspace of PT. Fesco Offshore has a length of 9 m, a width of 6 m and a height of 3 m with an average of 13 occupants/employees working with a total cooling load of 4627.921 W, a minimum total of 4227.921 W and a maximum total of 4827.921 W.